STUDYING THE DEVELOPMENT FACTORS OF STUDENTS’ CREATIVITY BASED ON Q-METHODOLOGY - Kazarenkov, Vyacheslav; Thuy, Bui; Kazarenkova, Tatyana; Kameneva, Galina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In educational science today, there are many studies on the factors associated with students' creativity using various research methods. A new feature of our current study is to use Q-methodology to explore the teacher's perspective on the factors influencing students' creativity in the teaching process. We investigated the views of 42 lecturers working at three universities in Vietnam including Hanoi National University of Education, Can Tho University of Medicine and Pharmacy, National University of Civil Engineering. Results of Q-sort implementation of participants are processed using a special software dedicated to Q-methodology – Ken-Q Analysis version 1.0.6. The results of the study indicated that there are two factors affecting the development of the students' creativity. Factor 1 extracted was named as the psychological characteristics of the students themselves. Factor 1 with an eigenvalue of 22.79 accounted for 54% of the study variance and consisted of 23 lecturers defining for this factor. Factor 2 was named as characteristics of the teaching activity of teachers. It accounted for 8% of the study variance with an eigenvalue of 3.38 and contained 19 lecturers. These factors accounted for 62% of the total study variance. The results are considered as important suggestions for teachers and students to achieve the purpose of developing creative personalities. Moreover, this also is an instruction for educational managers to improve the quality of education at universities.